Penentuan Setting Optimal Mesin Injection Moulding Menggunakan Metode Response Surface - Hidayat, Trifenaus Prabu; Sugioko, Andre; Catherine Williana (Prodi Teknik Industri, Fakultas Teknik - Universitas Katolik Indonesia Atma Jaya, 2024)
PT. Medion Farma Jaya is a company that produces livestock equipment, parts, and plastic packaging. One of the products produced by PT. Medion Farma Jaya is a 5-CC measuring spoon. This mass production process is based on what the company needs to package it with other products, or that can be from customer orders. This research is focused on the 5 CC measuring spoon product (SEN5CC) because, according to the company's 2021 historical data, there is a large percentage of rejected or defective products. Because of these problems, things can be done. The effect on the response to defective products is the setting of the injection Moulding machine by trial and error. Therefore, this research aims to find optimal settings for the machine for injection molding so that it can improve the quality of the product. To find out the optimal settings in this research, the response surface method was used. Based on this method is useful for getting the optimal level of factors or parameters that are significant to the response results. Based on research results, the factors used significantly influence optimal results, namely the melting temperature factor of 260 °C, holding pressure of 30 bar, and injection pressure of 62 bar. Therefore, the predicted response value was -25.1667, which meets the minimum target for the rejected product.